Implementation of 2% Employment Quota Policy for Persons with Disabilities in Surabaya City - Hidayati, Lila Rahma Nur; Widiyarta, Agus (UNIVERSITAS PAKUAN, 2025)
Persons with disabilities have equal rights to employment, including in the formal sector. However, people with disabilities often receive discriminatory treatment and experience obstacles in obtaining decent work. The government seeks to provide equal opportunities for people with disabilities by establishing a 2% quota policy for people with disabilities to work in the local government environment, as per Law 8/2016. This research aims to analyze the implementation of the 2% minimum quota policy for people with disabilities to work in the Surabaya City government, referring to the Van Meter Van Horn (1975) policy implementation theory. This research employs a qualitative case study approach, utilizing data collection techniques such as observation, interviews, and documentation. The results showed that: (1) Regarding policy standards and objectives, the Surabaya City Government has a clear legal foundation for implementing the policy; (2) Concerning resources, there are limitations in both human and financial aspects; (3) In terms of implementing organization characteristics, the government lacks a specific Standard Operating Procedure (SOP) to guide implementation; (4) Communication among implementing organizations is effective with proper policy dissemination and coordination with target groups; (5) Implementers’ attitudes are supportive, as seen from the agency's response to the acceptance of employees with disabilities; and (6) The social, economic, and political environment is generally favorable, although economic constraints remain a barrier. This research concludes that implementing the minimum 2% quota policy in the Surabaya City Government has not been fully optimal. This is primarily due to limited resources and the absence of structured procedures.